2012
DOI: 10.1186/1471-2288-12-117
|View full text |Cite
|
Sign up to set email alerts
|

What inference for two-stage phase II trials?

Abstract: BackgroundSimon’s two-stage designs are widely used for cancer phase II trials. These methods rely on statistical testing and thus allow controlling the type I and II error rates, while accounting for the interim analysis. Estimation after such trials is however not straightforward, and several different approaches have been proposed.MethodsDifferent approaches for point and confidence intervals estimation, as well as computation of p-values are reviewed and compared for a range of plausible trials. Cases wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…However, this maximum likelihood estimate (MLE) is biased. 2,3 Later, Jung and Kim 2 derived the uniformly minimum variance unbiased estimator (UMVUE) for the response rate by using the Rao–Blackwell theorem. They showed that the unbiased estimate has comparable efficiency when compared to the biased MLE.…”
Section: Introductionmentioning
confidence: 99%
“…However, this maximum likelihood estimate (MLE) is biased. 2,3 Later, Jung and Kim 2 derived the uniformly minimum variance unbiased estimator (UMVUE) for the response rate by using the Rao–Blackwell theorem. They showed that the unbiased estimate has comparable efficiency when compared to the biased MLE.…”
Section: Introductionmentioning
confidence: 99%
“…10 The use of the UMVUE to estimate RR is recommended as it addresses situations when the actual number of patients recruited is equal to or different from preplanned values. 3 The calculation of RR, p-values and CIs has been incorporated in open-access statistical libraries (packages "clinfun" and "OneArmPhaseTwoStudy", R statistical software) based on previously published methods 9,12 . We observed some differences between calculated (p-value) and simulated values (type I error). However, they were not relevant to the most common design constraints used in phase II single-arm trials (0.01 to 0.1 type I errors and 0.1 to 0.2 type II errors).…”
Section: Discussionmentioning
confidence: 99%
“…Two-stage designs are becoming increasingly more common, allowing for early trial termination in cases with low response rates (RRs) towards avoiding wasting time resources on ineffective treatments. 3 These trials aim to determine whether the new regimen is superior to a pre-speci ed RR (often 5%) 4 or experience with the standard of care, whereas the alternative hypothesis is that RR is somewhat higher, say 20%. 4 Nevertheless, the non-inferiority (NI) question might also be relevant in the phase II setting.…”
Section: Introductionmentioning
confidence: 99%
“…Porcher and Desseaux [ 3 ] considered different approaches for point and confidence intervals estimation, as well as computation of p-values for the same setting as KC. In their methods, the rankings used for computing p-values were based on estimators instead of likelihood.…”
Section: Introductionmentioning
confidence: 99%
“…They recommended the uniformly minimum variance unbiased estimator (UMVUE) as it exhibited good properties. In particular, when the second stage sample size is unaltered, they pointed out that the method based on UMVUE is equivalent to KC [ 3 ]. For this reason, our method should also improve on their methods.…”
Section: Introductionmentioning
confidence: 99%